An Empirical Analysis on the Factors that Influence Consumer Purchase Decisions in Sustainable Cosmetic Products (Journal of Informatics Education and Research, 2023)
Manufacturing cosmetic products is a highly chemical intensive process. Cosmetic products contribute to environmental abuse as chemicals, by products, plastics, paper, glass and metals are heavily used during the manufacturing to delivery process. Environmentally sustainable cosmetic products will cause less skin and environmental damage as the materials, manufacturing and recycling process employed are different compared to conventional systems. Consumers today are conscious about the detrimental effects of chemicals on health and hence there is a growing demand for sustainable cosmetic products. This paper aims to study the factors that affect consumer decision while buying sustainable cosmetic products. A five-point Likert Scale questionnaire was used to collect data from 256 consumers comprising of males and females using Simple Random Sampling. Product content, Product longevity, Product recyclability and Eco-labels are hypothesised to be major influencers in buying decisions among consumers. Multinomial Logistic Regression has been used to analyse the data and interpret the results. All factors have turned out to be significant in varying degrees. The study can assist cosmetic manufacturers in understanding what factors are crucial in influencing consumer decisions favouring or disfavouring a green product and thus design product-market-penetration strategies to enhance the acceptance of sustainable products.